Penerapan Strategi Pembelajaran Think Talk Write (TTW) Dalam Upaya Meningkatkan Aktivitas Dan Hasil Belajar Pada Siswa Kelas VI SD Negeri 5 Seraya Barat - Ni Wayan Sri Widiantari (Cetta: Jurnal Ilmu Pendidikan, 2019)
This research is motivated by the low learning of class VI students of SD Negeri 5 Seraya Barat on the subject of Hinduism Education, this is thought to be caused by several factors, including: learning that is still theoretical so students will easily feel bored and bored in receiving learning and learning teachers dominate the activities, so that they can eliminate the enthusiasm of students towards the learning material of Hinduism Education. This classroom action research was carried out in two cycles with the aim of increasing the activities and learning outcomes of Hinduism Education. The subjects of this research were 12th grade students of SD Negeri 5 Seraya Barat, consisting of 7 female students and 5 male students. Data is collected by observing activity and test results. The collected data is then analyzed using descriptive qualitative statistics. The results showed that the application of Think Talk Write (TTW) learning strategies in learning Hinduism Education can improve student activities and learning outcomes, namely student learning activities in Cycle I were 10.33 while student learning activities in cycle II were 14.00. Thus an increase of 3.67 from cycle I to cycle II, while on student learning outcomes in the first cycle is 79.58 and student learning outcomes in the second cycle is 88.33. Thus an increase of 8.75 from cycle I to cycle II. Based on these results, a number of suggestions can be recommended, namely: (1) Hinduism Education Teachers are expected to implement Think Talk Write (TTW) learning strategies in motivating students to improve learning achievement and (2) school principals are expected to fulfill learning facilities, such as books - Hinduism Education Books so that learning can run more optimally, (3) the application of Think Talk Write (TTW) learning strategies in this study is only limited to Cadhu Sakti material, it is suggested to future researchers to try to apply to different material and classes of this study